The role of vascular adhesion protein‐1 in diabetes and diabetic complications - Yen, I‐Weng; Li, Hung‐Yuan (Journal of diabetes investigation, 2024)
ABSTRACT Vascular adhesion protein‐1 (VAP‐1) plays a dual role with its adhesive and enzymatic properties, facilitating leukocyte migration to sites of inflammation and catalyzing the breakdown of primary amines into harmful by‐products, which are linked to diabetic complications. Present in various tissues, VAP‐1 also circulates in a soluble form in the bloodstream. Diabetes is associated with several complications such as cardiovascular disease, retinopathy, nephropathy, and neuropathy, significantly contributing to disability and mortality. These complications arise from hyperglycemia‐induced oxidative stress, inflammation, and the formation of advanced glycation end‐products (AGEs). Earlier research, including our own from the 1990s and early 2000s, has underscored the critical role of VAP‐1 in these pathological processes, prompting extensive investigation into its contribution to diabetic complications. In this review, we examine the involvement of VAP‐1 in diabetes and its complications, alongside its link to other conditions related to diabetes, such as cancer and metabolic dysfunction‐associated fatty liver disease. We also explore the utility of soluble VAP‐1 as a biomarker for diabetes, its complications, and other related conditions. Since the inhibition of VAP‐1 to treat diabetic complications is a novel and promising treatment option, further studies are needed to translate the beneficial effect of VAP‐1 inhibitors observed in animal studies to clinical trials recruiting human subjects. Besides, future studies should focus on using serum sVAP‐1 levels for risk assessment in diabetic patients, identifying those who need intensive glycemic control, and determining the patient population that would benefit most from VAP‐1 inhibitor therapies. Vascular adhesion protein‐1 (VAP‐1) has adhesive and enzymatic functions, aiding leukocyte migration to inflammation sites and producing by‐products linked to diabetic complications. This review focuses on the impact of VAP‐1 on diabetes and its complications, its association with related diseases, and the potential of soluble VAP‐1 as a biomarker.